Assessing policy coherence for developing a blue economy: a case study in the Republic of Panama - de Ycaza, Ricardo A.; Spalding, Ana K.; Cisneros-Montemayor, Andrés M. (Frontiers in Marine Science, 2024)
The blue economy approach to ocean governance promises environmentally sustainable, economically viable, and socially equitable ocean-based economic growth. However, the blue economy has been inconsistently defined, interpreted, and applied, often leading to incompatibilities between the blue economy approach and existing ocean policies. We explore the blue economy in the Republic of Panama, where recent government commitments include designing and implementing a blue economy approach to ocean sector development. We use qualitative text analysis and a policy coherence assessment to examine the consistency of objectives across existing ocean policies in Panama and their compatibility with broader blue economy goals. Our results indicate that Panama’s existing ocean policies address some blue economy goals but also reveal how policy coherence assessments and precise deliberation can inform a more contextually sensitive blue economy approach that aligns with existing ocean policies while also adding value to ocean governance and better integrating blue economy objectives. Findings suggest that Panama’s existing ocean policies could better address social, environmental, and resource use objectives, without disregarding the need to reinforce economic and governance goals; elevating social objectives, especially social equity, can truly differentiate Panama’s blue economy from its current ocean governance approach. Finally, while we acknowledge that greater policy coherence can potentially increase the likelihood of attaining policy objectives, our findings show that coherence alone does not ensure their realization in practice. Our study contributes to blue economy scholarship by providing the first Latin America-based case study using policy coherence to assess compatibilities between existing ocean policies and a blue economy. Other countries seeking to transition to a blue economy could use our findings to inform the design of their approach and its integration with their existing ocean policy frameworks.